PENINGKATAN KAPASITAS SDM KELOMPOK PETANI DALAM MENDUKUNG PROGRAM LUMBUNG PANGAN DI DESA TELANG SARI KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Ansori, Muslim; Rivai, Ahmad; Pusnita, Indah; Patima, Patima (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2022)
The food barn program is one of the national programs that has been running since 2020 until today. To support the sustainability of the food barn program, it is important to involve the role of farmers, so it is necessary to equip farmers with training to increase the capacity of human resources (HR) of farmer groups, which is a need that must be implemented immediately, so that it can encourage sustainable development, food security and increase farmer welfare. as well as society. Training activities were carried out at the Telang Sari Village Hall, Tanjung Lago District, with the implementing method using the Participatory Rural Appraisal (PRA) approach and techniques consisting of location surveys, observations, FGDs and training for farmer groups. Training activities on the use of technology have a positive impact on farmer groups and the community, namely that these groups can become more independent and confident in responding to various agricultural challenges. Thus, technology training for farmers allows the food barn program to maximize the potential of farmer groups, increase food security, and have a positive impact on the Telang Sari Village community and farmer welfare.